2013
DOI: 10.1177/1059601112473815
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Identity and Organizational Identification

Abstract: In this article, we present an overview of the literatures on organizational identity and organizational identification. We provide overviews of four major approaches to organizational identity: functionalist, social constructionist, psychodynamic, and postmodern. The literature on organizational identification, by contrast, exhibits greater consensus due to the hegemonic power of social identity theory, and is predominantly functionalist. We review recent research on organizational identification regarding pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 342 publications
(116 citation statements)
references
References 157 publications
(222 reference statements)
4
107
0
5
Order By: Relevance
“…It has also been shown to be more valued and consistent over time than supervisor support (Ng & Sorensen, 2008). At the organizational level, it has been suggested that leader-member (supervisor-employee) exchange is an important resource that promotes employees' identification with and positive emotions towards their overall organization (He & Brown, 2013;Tangirala, Green, & Ramanujam, 2007). Social support from supervisors (defined as the interpersonal transfer of instrumental or emotional resources from the supervisor to the employee) has been shown to strengthen employees' emotional attachments to their employing organization (Rousseau & Aubé, 2010).…”
Section: Job Resources Related To Group-based Pridementioning
confidence: 99%
“…It has also been shown to be more valued and consistent over time than supervisor support (Ng & Sorensen, 2008). At the organizational level, it has been suggested that leader-member (supervisor-employee) exchange is an important resource that promotes employees' identification with and positive emotions towards their overall organization (He & Brown, 2013;Tangirala, Green, & Ramanujam, 2007). Social support from supervisors (defined as the interpersonal transfer of instrumental or emotional resources from the supervisor to the employee) has been shown to strengthen employees' emotional attachments to their employing organization (Rousseau & Aubé, 2010).…”
Section: Job Resources Related To Group-based Pridementioning
confidence: 99%
“…Social movement scholarship provides meaningful insight into the formation of collective identity, how it is defined, and what impact it has on the individuals who occupy these spaces as well as the community at large (He & Brown, 2013). Attempts at examining collective identity have prompted scholars to offer several definitions.…”
Section: Boundary Work In Social Movement Organizationsmentioning
confidence: 99%
“…EI is defined as the component of identity that is related to the job or task content. This concept has been overlooked in empirical studies (Tang et al, 2014), whereas OI has received considerable attention in organization studies (He & Brown, 2013). The latter concept refers to an entity's attempt to define itself (Corley et al, 2006, p. 87) and is related to a firm's culture, history, structure, characteristics, status and reputation (Martin, Johnson, & French, 2011).…”
Section: The Influence Of Social Identity On Both Creative Idea Assmentioning
confidence: 99%